HUBUNGAN ANTARA TINGKAT PENGETAHUAN IBU TENTANG MANFAAT ASI DAN STATUS PEKERJAAN DENGAN LAMANYA MENYUSUI DI DESA KRINGIKAN - Sri Aminingsih; Anis Dwi Yuliastuti (KOSALA : Jurnal Ilmu Kesehatan, 2017)
Background : age 0-24 months is a period of rapid growth and development which is wellknown as "golden period" or "critical period". WHO / UNICEF has recommended fourimportant things to be done: breastfeeding the baby immediately within 30 minutes afterthe baby is born, giving only breastmilk or exclusive breastfeeding from birth to 6 monthsold baby, providing complementary food from infants aged 6 months to 24 months andcontinue breastfeeding until the child is 24 months old or older. The purpose to analyzethe relation between mother's knowledge level about the benefit of breastfeeding andmother's employment status with duration of breastfeeding in Kringikan Village. Thepopulation of this study were mothers with children aged 2-5 years which accounted for45 childrens.Methods of this research is correlation with cross sectional method.Results : the majority of respondens had high level of knowledge which accounted for84.4%. The majority of mothers was unemployed which accounted for 82.2% and themost duration of breast feeding was more than 2 years which accounted for 84.4%.Conclusion : from the analysis of logistic regression of mothers test about the relationshipof knowledge level about breastfeeding benefit, the employment status toward theduration of breastfeeding showed there was a positive and statistically significantrelationship between the knowledge level of breastfeeding benefit and the employmentstatus as much as 42.2% on the duration of breastfeeding. The other 57.8% is influencedby other factors.Keywords: Knowledge, the status of mother employment and duration of breastfeeding.